PENGARUH ALOKASI ANGGARAN PENDIDIKAN, KESEHATAN DAN INFRASTRUKTUR JALAN DESA TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN SEKADAU - HADI SALAHUDIN, YARLINA YACOUB DAN (Jurnal Ekonomi Daerah (JEDA), 2013)
ABTRACT The result of descriptive analisisis about relationship among Education Budget Allocation (X1it), Health Budget Allocation (X2it), and Silvan Road Budget (X3it) with economic growth at any given district (Yit) pointing out varying pattern, and step-up happening that don't proportional good X 1it , X 2it , and also X 3it to Yit (economic growth) in Sekadau Regency. Of estimation result by use of data regression method pane points out, of 3rd variable X1 , X2 , and X3 on confidence zoom 95%(?=0,05), just X2 (health budget) one that positive ascendant and signifikan to economic growth (Yit ) with regression coefficient as big as 2,388. Its mean each increase X2 1%, will increase economic growth as big as 2,388%. Variable X1 (education budget) having for negative but not signifikan with regression coefficient(-0,271), its mean if happening added one percent education budget, will down economic growth percentage as big as 0,271%. For Budget allocation Clears A Root Village (X 3 ) also well worth negative(-1,40) and signifikan, with regression coefficient as big as -1. 419772 , negative subjective happening among Yit and x 3 . Its mean each budget allocation increase clears a root village as big as 1% will beget economic growth percentage decrease as big as 1,4 19772 %. Of Quiz result (uji F) on confidence zoom 95% (? =0,05), pointing out influence that signifikan, namely assesses Fcomputing = 9,121139 greater of appreciative Ftable = 2,60 and probability (sig f) = 0,00012 (smaller of 0,05), its mean (X1it, X2it, and X 3it ) simultan's ala having for/signifikan to Yit, with Determinant coefficient (R 2 ) as big as 0.4186, its mean is affecting that is given of variable third that (X 1it , X 2it , and x 3it ) as big as 41,86% meanwhile its rest (58,14%) regarded by other factor. Key word: Economic growth, Education, Health, Infrastructure